2007
DOI: 10.1093/nar/gkm579
|View full text |Cite
|
Sign up to set email alerts
|

Single-stranded DNA ligation and XLF-stimulated incompatible DNA end ligation by the XRCC4-DNA ligase IV complex: influence of terminal DNA sequence

Abstract: The double-strand DNA break repair pathway, non-homologous DNA end joining (NHEJ), is distinctive for the flexibility of its nuclease, polymerase and ligase activities. Here we find that the joining of ends by XRCC4-ligase IV is markedly influenced by the terminal sequence, and a steric hindrance model can account for this. XLF (Cernunnos) stimulates the joining of both incompatible DNA ends and compatible DNA ends at physiologic concentrations of Mg2+, but only of incompatible DNA ends at higher concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 27 publications
3
94
0
Order By: Relevance
“…The crystal structure of the L4-X4-Cernunnos complex with the fulllength proteins should help to clarify the binding mode of the complete ligation complex. DSB repair studies in the presence or absence of Cernunnos have shown that Cernunnos promotes DNA end ligation by the L4-X4 complex (25,33). From our observation, we propose that the oligomerization of the X4-Cernunnos complex could be a mechanism to facilitate the recruitment of two or more L4-X4 complexes to DNA DSB repair points (Fig.…”
Section: Discussionmentioning
confidence: 55%
“…The crystal structure of the L4-X4-Cernunnos complex with the fulllength proteins should help to clarify the binding mode of the complete ligation complex. DSB repair studies in the presence or absence of Cernunnos have shown that Cernunnos promotes DNA end ligation by the L4-X4 complex (25,33). From our observation, we propose that the oligomerization of the X4-Cernunnos complex could be a mechanism to facilitate the recruitment of two or more L4-X4 complexes to DNA DSB repair points (Fig.…”
Section: Discussionmentioning
confidence: 55%
“…The Artemis resection in 2-to 6-nt increments at blunt ends, as in Fig. 2, may liberate these short oligonucleotides, allowing them to be religated via the single-strand ligation activity of the ligase IV complex (22). This would generate the short inverted repeats observed at partially resected coding ends (27), which have previously been difficult to explain mechanistically until now.…”
Section: Discussionmentioning
confidence: 98%
“…The final stage of DSBs repair by NHEJ is binding the broken DNA ends by the ligase complexes (Mahaney et al, 2009;. In the presence of Ku proteins, the full ligase complex (XRCC4/DNK-ligase IV/XLF) can couple incompatible DNA ends and, more effectively, blunt ends of breaks (Gu et al, 2007). Thus, we can assume that the main mechanism for repairing DNA DSB induced by low doses of IR is the NHEJ pathway.…”
Section: Repair Of Dna Double Strand Breaksmentioning
confidence: 99%